Pengembangan Media Ludo Digital Materi Tanggung Jawab Siswa Pada Mata Pelajaran PPKn Kelas V SD - Handak, Indira Syifa Karai; Dewi, Dinie Anggraeni; Sutisna, M.Ridwan (Lembaga Intelektual Muda (LIM) Maluku, 2024)
This research is motivated by technological developments in the world of education today, namely in the era of revolution 4.0. This of course makes teachers have to be more creative in carrying out learning. This digital learning media is very relevant to the age development of elementary school children, especially grade V. The development of this digital ludo media uses a platform that geniuses use the Design and Development method. The research procedure to be used in research is the ADDIE model development procedure (Analysis, Design, Development, Implementation, Evaluation). The validation test procedures and responses of material experts, media experts and linguists according to indicators refer to BSNP 2017 and are modified based on research needs. This received a very good response and deserves to be tested on elementary school students with a percentage of results of 96.02%. The response of students, users and teachers received a positive response with an accumulation percentage of 96.65%. Based on several responses, this digital ludo media obtained results that are very worthy of use in learning and received positive responses from students, users and teachers in teaching and learning activities